2003
DOI: 10.1016/s1074-7613(03)00152-3
|View full text |Cite
|
Sign up to set email alerts
|

B7-H4, a Molecule of the B7 Family, Negatively Regulates T Cell Immunity

Abstract: We identify a B7 family molecule, B7-H4, by protein sequence analysis and comparative molecular modeling. While B7-H4 mRNA is widely distributed in mouse and human peripheral tissues, cell surface expression of B7-H4 protein is limited and shows an inducible pattern on hematopoietic cells. Putative receptor of B7-H4 can be upregulated on activated T cells. By arresting cell cycle, B7-H4 ligation of T cells has a profound inhibitory effect on the growth, cytokine secretion, and development of cytotoxicity. Admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
738
4
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 637 publications
(779 citation statements)
references
References 38 publications
29
738
4
3
Order By: Relevance
“…Inhibitory B7 molecules have been demonstrated to be upregulated in different tumors, which may contribute to tumor immune evasion (Chen, 2004). B7-H4, a member of the B7 family, has been identified as a negative regulatory molecule on the cell membrane, which inhibits the proliferation and cytokine production of CD4+ T and CD8+ T cells (Prasad et al, 2003;Sica et al, 2003). In the tumor microenvironment, B7-H4 binds to an unknown receptor on the T cell surface, inhibiting tumor-specific T cell activation and proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitory B7 molecules have been demonstrated to be upregulated in different tumors, which may contribute to tumor immune evasion (Chen, 2004). B7-H4, a member of the B7 family, has been identified as a negative regulatory molecule on the cell membrane, which inhibits the proliferation and cytokine production of CD4+ T and CD8+ T cells (Prasad et al, 2003;Sica et al, 2003). In the tumor microenvironment, B7-H4 binds to an unknown receptor on the T cell surface, inhibiting tumor-specific T cell activation and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent report showed that host B7-H4 may enable metastasizing cancer cells to escape local antitumor immune responses through interactions with the innate and adaptive immune systems (Abadi et al, 2013). Several evidences have demonstrated that the B7-H4 molecule promotes cancer progression via regulating T cell mediated antitumor immunity (Zang et al, 2003;Sica et al, 2003;Sun et al, 2012). Previous studies have showed that the higher expression of B7-family inhibitory molecules by tumor cells is significantly correlated with densities of TILs in human malignancies, such as gastric cancer and esophageal squamous cell carcinoma ( Miyatake et al, 2007;Arigami et al, 2011;Chen et al, 2011;Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Ligation of B7-H4 has been demonstrated to inhibit T-cell proliferation and IL-2 production, while inhibition of B7-H4 in preclinical animal models resulted in enhanced cytotoxic alloantigen-specific T-cell responses. 98 Administration of anti-PD1 Ab has been found to have an impact on overall survival in patients with advanced melanoma. 99 It should be noted however that Abmediated blockade of coinhibitory signals may be accompanied by adverse events in the form of autoimmune reactions.…”
Section: Immunomodulatory Antibodiesmentioning
confidence: 99%
“…Co-stimulation is balanced by co-inhibitory signals, which ultimately determines whether the T cell response is activating or inhibitory. 1 The B7 family of immunoglobulins has 10 reported members, which function as important secondary signals to either co-stimulate or co-inhibit T cells by selectively binding to T cell ligands, with B7-H2, B7-H6 and B7-H7 stimulating activation of naive T cells; [2][3][4] B7-DC, B7-H4 and B7-H5 inhibiting T cell responses; [5][6][7] and B7-1 and B7-2 providing both stimulatory and inhibitory signals. [8][9][10] Under normal circumstances, costimulators facilitate the development of protective immunity via receptors such as CD28 and CD28H, 9,11 whereas co-inhibitors including CTLA-4 and PD-1 inhibit inflammation to avoid over-activation.…”
Section: Introductionmentioning
confidence: 99%